The Income Inequality in the Fastest Growing Economies - Mavrov, Hristo (Research Papers, 2021)
The impact of accelerated growth on inequality has not been sufficiently studied in the literature. The purpose of the article is to investigate the link between accelerated economic development and income inequality. The period 1870-2016 is considered, and the countries with the highest rate of GDP growth per capita are highlighted using a comparative analysis. The evolution of inequality over this period is examined and it is proved that it is possible to achieve accelerated economic growth and catching-up without increasing income inequality and even reducing it.